Weber approach for retromolar adenoid cyst carcinoma: case report and literature review - Ruíz, Emmanuel Stephano Bracho; Martínez, Daniel Benito Castillo; Tapia, Sergio Sandoval; Ramírez, Daniela Rodríguez; Barragán, Cuautemoc Aguilar; Avendaño, Luis Bernardo Gómez; Aguilar, Laura Yossune León; Ramírez, Miguel Angel Monroy; Flores, Rafael Silva (International Journal of Research in Medical Sciences, 2023)
Adenoid cyst carcinoma (ACC) is an uncommon facial tumor and challenging to treat; surgical treatment is challenging due to its localization. A 49-year-old Latin female patient with a one-year history of soft tissue-depending mass of slow growth in the right maxillary region. Laboratory tests reported normal. Contrast-enhanced computed tomography showed a maxillary tumor. Patient underwent to surgical resection by Weber-Fergusson approach. The patient received postoperative adjuvant radiotherapy. ACC is a challenging entity to treat, surgical resection, and radiotherapy is required. The combination of surgery and radiotherapy represents the definitive treatment for ACC. Chemotherapy remains controversial and is reserved for palliation in selected cases.